Assessment of water eutrophication in Kampar campus - Chan, Desmond Min Pin (2019)
Eutrophication also known as algae blooming when a water body enrich with nutrients such as phosphorus and nitrogen. Eutrophication can be natural process and anthropogenic process that accelerate the natural process by discharging sewage, agriculture runoff and industrial waste. This study investigated the overall trophic state of University Tunku Abdul Rahman (UTAR) lake, Kampar Campus Lake by using Carlson’s Trophic State index (CTSI). Water sampling was taken from five collection points with different inlet and outlet from other sources (lakes or drains). There were several parameters had been examined such as in-situ test (dissolved oxygen, water temperature, pH value, turbidity and water transparency) and laboratory tests (total nitrogen, total phosphorus, chlorophyll-a, ammonia, and chemical oxygen demand). The data collection included the rainy season began from October 2018 to December 2018, and the dry season with a low rainfall rate started from January 2019 to March 2019. The highest Secchi Disk Transparency of 1.24 ± 0.05 m and the lowest chlorophyll-a concentration of 23.07 ± 2.28 µg/L at site 2 (centre of lake) compared to the low Secchi Disk Transparency of 0.81 ± 0.03 m and the highest chlorophyll-a concentration of 41.03 ± 5.27 µg/L at site 4 (cafeteria). The site 2 has a high water transparency due to less algae biomass and the absent of discharge inlet and outlet, meanwhile site 4 exposed to high discharged rate from the cafeteria causing a massive algae blooming. The Secchi Disk Transparency was inversely proportional to the chlorophyll-a concentration. The total phosphorus indicated that November 2018 have the highest concentration of 95 ± 5.7 µg/L due to high rainfall resulted runoff to the lake. The other parameters were compared to the Water Quality Index and it showed that the UTAR Kampar lake was classified as Class III (moderate). Thus, UTAR Kampar lake was nutrient pollution that causes eutrophication.